Survey of Pharmacoeconomic Assessment Activity in Eleven Countries - Dickson, Michael (OECD Health Working Papers, 2003)
Policy-makers responsible for publicly-funded drug programmes face continual pressures between the demand to accommodate a steady stream of new and more effective drugs and the ongoing requirement to control costs. In the face of these pressures, a growing number of OECD countries are applying 'pharmacoeconomic assessment' (health technology assessment for drugs) - to new drugs to guide decisions about accepting such products for reimbursement under their public programme, or to inform negotiations about pricing. This paper provides an analytical overview of the developing practice of pharmacoeconomic assessment in eleven OECD countries. It looks at the objectives of the activity, some of its processes and some of its impacts. It does this by drawing on a literature review and on an exploratory survey of the activities of pharmacoeconomic agencies in the eleven countries. It also reviews briefly the state of pharmacoeconomic assessment in the United States. The main conclusions are as ...